2004
DOI: 10.1002/jcb.20117
|View full text |Cite
|
Sign up to set email alerts
|

Annexin 2 expression is reduced in human osteosarcoma metastases

Abstract: Osteosarcoma is an aggressive primary bone cancer affecting primarily children and young adults. The development of valuable diagnostic indicators and therapeutic agents will be enhanced by the identification and characterization of genes that contribute to its aggressive behavior. We used representational difference analysis to isolate genes differentially expressed between primary human osteosarcoma tumors and subsequent metastatic lung lesions to identify genes potentially involved in metastatic potential. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 43 publications
3
46
0
1
Order By: Relevance
“…Meanwhile, recent research results indicated that A3 expression in the tissues of patients with cisplatin-resistant prostate cancer and ovarian cancer has increased significantly. In addition, the cycles of patients without tumors in the A3 high expression group are clearly shortened (Gillette et al, 2004;Huang et al, 2008) Related studies also prove that A3 produces drug resistance by reducing the platinum content, the platinum-DNA combining quantity within cells, and the p53 level in ovarian cancer cells (Yan et al, 2010). The tumorigenesis of cells with high A3 expression is significantly increased after cisplatin treatment, as demonstrated through an animal experiment.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Meanwhile, recent research results indicated that A3 expression in the tissues of patients with cisplatin-resistant prostate cancer and ovarian cancer has increased significantly. In addition, the cycles of patients without tumors in the A3 high expression group are clearly shortened (Gillette et al, 2004;Huang et al, 2008) Related studies also prove that A3 produces drug resistance by reducing the platinum content, the platinum-DNA combining quantity within cells, and the p53 level in ovarian cancer cells (Yan et al, 2010). The tumorigenesis of cells with high A3 expression is significantly increased after cisplatin treatment, as demonstrated through an animal experiment.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, A2 promotes the invasion and metastasis of lung cancer cells. However, no statement has been made regarding its relationship with cisplatin-resistance in adenocarcinoma (Gillette et al, 2004;Huang et al, 2008). Meanwhile, recent research results indicated that A3 expression in the tissues of patients with cisplatin-resistant prostate cancer and ovarian cancer has increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin A2 shows increased expression in several type of cancer, including renal cell cancer (Zimmermann et al, 2004a), breast cancer (Sharma et al, 2006) and sarcomas (Gillette et al, 2004;Syed et al, 2007), and there are several possible mechanisms by which annexin A2 may be involved in tumour progression. Annexin A2 interacts with tissue-type plasminogen activator and disruption of this interaction resulted in decreased tumour cell invasion (Rand, 2000;Diaz et al, 2004;Sharma et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of annexin A2 has been found in renal cell cancer, where it is associated with tumour stage (Zimmermann et al, 2004a), invasive breast cancer (Sharma et al, 2006) and sarcomas, including both soft tissue sarcomas (Syed et al, 2007) and osteosarcomas (Gillette et al, 2004). There is increased expression of annexin A4 in renal clear cell carcinoma (Zimmermann et al, 2004b).…”
mentioning
confidence: 99%
“…Upregulation of ANX2 expression has been reported in hepatocellular carcinoma (Frohlich et al, 1990), lung cancer (Cole et al, 1992), pancreatic cancer (Diaz et al, 2004;Esposito et al, 2006), breast cancer (Sharma et al, 2006), gastrointestinal cancer (Singh, 2007), glioma (Reeves et al, 1992) and colorectal cancer (Emoto et al, 2001b). Conversely, downregulation of ANX2 expression has been reported in prostate cancer (Chetcuti et al, 2001;Banerjee et al, 2003;Liu et al, 2003), osteosarcoma (Gillette et al, 2004), oesophageal squamous cell carcinoma (SCC) (Zhi et al, 2003) and head and neck SCC (Pena-Alonso et al, 2008). This discrepancy may be explained by ANX2 expression in the histological origin of tumours, the cellular localisation and the putative function of ANX2 in tumour cells.…”
Section: Discussionmentioning
confidence: 99%